THE STATE GUARANTEES PROGRAM OF FREE MEDICAL CARE: APPROACHES TO STANDARDIZE THE COSTS OF MEDICAL CARE - Yu. A. Ledovskikh; E. V. Semakova; M. V. Avksent’eva (Фармакоэкономика)
According to the current legislation, the standards of medical care lay the ground for the development of a program on state guarantees (SGP) to deliver free medical care to the citizens. While this standard provides an opportunity for calculating the costs of implementing the SGP, the past experience indicates the need for changes to produce new standards that would consider the “completed treatment” factor. The article proposes approaches to updating the standards and improving the methodology of cost calculation. In addition, this analysis is expected to help optimize the cost of medical care in various clinical and statistical groups.